Novel Sodium Channel Inhibitor From Leeches - Wang, Gan; Long, Chengbo; Liu, Weihui; Xu, Cheng; Zhang, Min; Li, Qiong; Lu, Qiumin; Meng, Ping; Li, Dongsheng; Rong, Mingqiang; Sun, Zhaohui; Luo, Xiaodong; et al. (Frontiers in Pharmacology, 2018)
Considering blood-sucking habits of leeches from surviving strategy of view, it can be hypothesized that leech saliva has analgesia or anesthesia functions for leeches to stay undetected by the host. However, no specific substance with analgesic function has been reported from leech saliva although clinical applications strongly indicated that leech therapy produces a strong and long lasting pain-reducing effect. Herein, a novel family of small peptides (HSTXs) including 11 members which show no any similarity with known peptides was identified from salivary glands of the leech Haemadipsa sylvestris. A typical HSTX is composed of 22-25 amino acid residues including 4 half-cysteines, forming two intra-molecular disulfide bridges, and an amidated C-terminus. HSTX-I exerts significant analgesic function by specifically inhibiting voltage-gated sodium (NaV) channels (NaV1.8 and NaV1.9) which contribute to action potential electrogenesis in neurons and potential targets to develop analgesics. This study reveals that sodium channel inhibitors are analgesic substances in the leech. HSTXs are excellent candidates or templates for development of analgesics.